PERKEMBANGAN OBLIGASI SYARI’AH (SUKUK) DI INDONESIA: SUKUK MUSYARAKAH DAN ISTISHNA - Megasyara, Ira (Jurnal Akuntansi AKUNESA, 2014)
Sukuk is one of the Islamic product in Indonesia capital market is limited, but still has the potential to be developed both in terms of quantity and type of contract. Sukuk issued in Indonesia is currently only using 2 (two) contract, the ijarah and mudharabah contract. In order to expand alternative means of financing for the company and for investors to invest in the Islamic capital market products, the possible use of alternative contract in sukuk structures in Indonesia, the Musyarakah agreement and istishna contract. The second contract has been widely used in sukuk issuance in the international capital markets. The both contract has been widely used in sukuk issuance in the international capital markets. In Indonesia, the use of contract musyarakah sukuk has the potential to be applied by companies in various sectors of the business. While the use of contract istishna sukuk, used for companies in the infrastructure sector. Keyword: Sukuk musyarakah,sukuk istishna